Christianity in Britain Since 1914
XVII, 314 p. 13 illus., 8 illus. in color.
Keywords: ‘The general view that Christianity in Britain has been in decline since the First World War is challenged in this book. Local studies show that, alongside decay, vibrant new communities of faith have sprung up, especially in cities and among minority ethnic populations. Recent church history has been drastically revised.’ -David Bebbington, University of Stirling, UK ‘Detail matters in the study of religion. So do real people in real churches in rapidly changing environments. All of the above abound in these chapters - I recommend them very warmly.’ -Grace Davie, University of Exeter, UK ‘These meticulously researched studies of specific localities and organizations make an important contribution to our understanding of Christianity in the UK over the last century, by showing how an overarching narrative of secularization and church decline is often at odds with realities on the ground.’ -John Wolffe, The Open University, UK This book charts the profound changes in British Christianity over the last century. It does so through the medium of diverse local case-studies, based on high quality new research. The ethnic diversification of British churches in the last fifty years is a key theme of the volume. Overall, the chapters show how secularization has had different trajectories in different parts of the country. Alongside this, the book charts the surprising desecularisation of parts of Britain in recent decades. David Goodhew is a Visiting Fellow of St Johns College at Durham University, UK and Vicar of St Barnabas Church, Middlesbrough, UK. Mark Smith is Associate Professor at the University of Oxford, UK.